Pemasangan Lampu Jalan Berbasis Solar Cell untuk Penerangan Jalan di Desa Cilatak Ciomas - Septianissa Azzahra; Christiono Christiono; Samsurizal Samsurizal; Miftahul Fikri; Titi Ratnasari; Rizki Pratama Putra; Dhami Johar Damiri (Terang, 2019)
The negative impact of fossil-fueled plants and the lack of public understanding of renewable energy lies behind the holding of these PKM activities with the aim of educating and at the same time transferring technology that is directly beneficial to the community in the form of solar powered street lighting. From the surveys that have been conducted where there are no available street lighting facilities so that there are some community activities that are difficult to do at night. From this work, there were two important things, among others, that the community gained an understanding of renewable energy and knowledge to efficiently use energy to reduce the environmental impact of the dominant fossil power plant in Indonesia. The second is that with the help of solar-powered street lights, the community is very helpful in carrying out activities at night and creates more secure conditions in the community.